Kinematics Analysis of 2-PrRS-PR(P)S Parallel Metamorphic Mechanism - Kun Ma; Hongwei Ma; Haibo Tian; Gang Dong (Jixie chuandong)
A novel parallel metamorphic mechanism of 2-PrRS-PRS mechanism that can change the orientations of the axis of the revolute pair is designed based on the theory of metamorphic mechanism that change the orientation of kinematic pairs can lead to configuration transformation. This mechanism consists of three kinematic chains fixed on base plate and moving plate. To change the output and workspace, the revolute pair of two kinematic chains can change its rotation axis by the prismatic pair which is the drive pair. According the characteristic of the mechanism, the degree of freedom is analyzed using the screw theory. By using closed vector method and geometric constraint, the forward position and the inverse solution of the mechanism are built, and the velocity and acceleration equation of the mechanism are obtained by derivation. By using Matlab, the parameters of the mechanism and positions are substituted into, the forward and inverse solutions are solved, the figure of position and orientation is drawn. The correctness of theoretical analysis is verified by Adams simulation.